NILAI-NILAI BUDAYA MASYARAKAT WAKORUMBA SELATAN DALAM CERITA RAKYAT NGKAA-NGKAASI - Fina Amalia Masri; Wa Ode Halfian (BASIS (Bahasa dan Sastra Inggris), 2020)
This paper discussed the cultural values of the South Wakorumba Society in the Ngkaa-ngkaasi folklore. This paper is motivated by the beginning of a reduction in public awareness of the presence of folklore in everyday life. Folklore, which contains a lot of good values, it should stay alive and be preserved in society. On the other hand, the source of the folklore of the elderly people who have mostly died will be increasingly disappeared because these parents may not necessarily pass this story on to their children and grandchildren. So, it is feared that this folklore will become extinct. This paper aimed to describe the cultural values of the South Wakorumba community in the Ngkaa-ngkasi folklore. This paper was analyzed by using qualitative descriptive methods. Data collection techniques used was recording techniques, observation techniques, and interview techniques. The sources of the research data were the elderly people in South Wakorumba sub-district who know the folklore that lives and develops in the community. The results of data analysis showed that there are cultural values of the South Wakorumba community in the Ngkaa-ngkasi folklore, namely cultural values about human relations as individuals (acting calm and unhurried, adding to life knowledge, and fostering personal discipline), cultural values about human relations with humans (please help in kindness, being generous, and deliberation), and cultural values about human relations with nature (utilizing nature).